The Impact of Machine Translation on Vocabulary Acquisition and Reading Comprehension in ESL Learners - Lawal Ismaeel Abimbola (Yayasan Kyadiren, 2023)
This study investigated the impact of using machine translation on vocabulary acquisition and reading comprehension in English as a Second Language (ESL) learners. A total of 60 undergraduate students enrolled in an ESL course were randomly assigned to either an experimental group that used Machine Translation during language learning activities or a control group that did not use Machine Translation. Results showed that the experimental group outperformed the control group in vocabulary acquisition and reading comprehension, while also experiencing a higher cognitive load. The study suggests that while Machine Translation can be a useful tool for ESL learners, it should be used with caution and guidance to prevent negative effects on cognitive load.